Pragmatic Analysis of Flouting Grice’s Maxims in Indonesian and US Presidential Debates - Abi, Maria; Syahid , Agus; Syamsurrijal; Rahmawati, Lela; Hastuti, Hilda (LPPM Universitas Dhyana Pura, 2025)
This study examines the flouting of Grice’s cooperative maxims, specifically Quantity, Relevance, Quality, and Manner in the 2024 presidential debates of Indonesia and the United States. The objective is to identify the types of maxim flouting committed by candidates and to compare pragmatic communication strategies across these two distinct political cultures. A qualitative descriptive approach was employed, using transcripts from YouTube videos of the presidential debates in Indonesia and the U.S. Data collection involved observation, transcription, and documentation, while data analysis focused on classifying and presenting instances of maxim flouting. The analysis centers on how candidates strategically flout these maxims to achieve rhetorical goals within formal debate settings. The findings revealed a total of 20 instances of maxim flouting, with the Maxim of Quantity and the Relevance being the most frequently flouted. This flouting serves to control the narrative, divert difficult questions, and strengthen the political image. Donald Trump flouted the most maxims (7 instances), followed by Prabowo Subianto (5), Kamala Harris and Ganjar Pranowo (4 each), while Anies Baswedan did not flout any maxims. The communication style of U.S. candidates tends to be more expansive and confrontational, whereas Indonesian candidates tend to be more structured and concise.